Massively parallel cuckoo pattern matching applied for NIDS/NIPS - Thinh, Tran Ngoc; Kittitornkun, Surin (My University, 2010)
This paper describes a Cuckoo-based Pattern Matching (CPM) engine based on a recently developed hashing algorithm called Cuckoo Hashing. We implement the improved parallel Cuckoo Hashing suitable for hardware-based multi-pattern matching with arbitrary length. CPM can rapidly update the static pattern set without reconfiguration while consuming the lowest amount of hardware. With the power of massively parallel processing, the speedup of CPM is up to 128X as compared with serial Cuckoo implementation. Compared to other hardware systems, CPM is far better in performance and saves 30% of the area. © 2010 IEEE.
Keywords: Cuckoo hashing; FPGA; Massively parallel processing; NIDS/NIPS; Pattern Matching